STRATEGI PENDAYAGUNAAN ZAKAT PRODUKTIF (Studi BAZ Kabupaten Sukabumi Jawa Barat) - Aab Abdullah (Institut Agama Islam Sahid Bogor, 2021)
Zakat is one of the main components in the Islamic economic system, it is a driving force for the balance between the rich and the poor. Its position is increasingly indispensable when faced with socio-economic problems that are not in favor of the poor. As a social control for zakat, there is no excessive difference between the rich and the poor, it makes the wealth not only revolve around the rich, as mentioned in QS. Al-Hasyr verse 7. Zakat is so beneficial that Caliph Abu Bakr fought people who did not want to pay zakat. The zakat problems faced today are very complex, starting from the fact that there are still some people who do not want to pay zakat, the distribution of zakat that has not been well organized to the fiqh problems regarding development and ijtihad for productive zakat models. It is this last problem that is the subject of this paper. Productive zakat is to make zakat money not only consumptive in the sense that it is consumed immediately, but zakat assets are used for business capital so that it can alleviate the poverty of mustahik zakat. With this business capital, it is hoped that mustahik zakat will one day become a muzaki. The zakat management strategy carried out by BAZ Sukabumi City is in the form of capital